Method for determination of the absorption coefficient in films based on photoluminophore suspension for white LEDs - Khmil, D.N.; Kamuz, A.M.; Oleksenko, P.F.; Kamuz, V.G.; Aleksenko, N.G.; Kamuz, O.A. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2015)
Developed in this work is the method for measuring the absorption coefficient in optically non-homogeneous media (films prepared from photoluminophore suspension). Using this new method, the authors have measured the absorption spectrum of the above films with inorganic photoluminophore FLY-7. At the film absorption peak (near 448 nm) and photoluminophore concentration close to 20%, the absorption coefficient reaches 124 cm⁻¹. Ascertained have been the conditions that should be provided when using this method.